The relationship between job burn-out and the job leakage of male and female administrators – A comparative study between King Abdulaziz University and Jeddah University – - Al-hindi, Heba Mohammed; Al-qurashi, Suzan Mohammed (Journal of Economic, Administrative and Legal Sciences, 2021)
This study analyzes the reality of Occupational combustion in employees and employees working at King Abdulaziz University in Jeddah and Jeddah University, where the problem of the research is to identify the effect of Occupational combustion on the leakage of employees and female administrative and administrative departments in both King Abdulaziz University and Jeddah University the research aims to identify job stress and its impact The research also relied on the distribution of a questionnaire form, and a statistical analysis of the resolution on a random sample and the study community of administrators and administrators at King Abdulaziz University and the University of Jeddah, which number (640)employees and employees, and the study assumed that there are statistically significant differences between the dimensions of the burn job and: There are direct significant differences between functional leakage and functional stress, at Pearson R correlation coefficient (0.732) with an estimated semantic value (0.001) which is a statistical function, and there are direct significant differences between functional leakage and the human element, and at Pearson R correlation coefficient (0.721) with an estimated semantic value (0.001) which is a statistical function, there are inverse, At the Pearson correlation coefficient R (-0.203) with an estimated semantic value of (0.001), which is a statistical function, there are significant differences according to the workplace variable in the two-dimensional functional combustion (functional stress – Feeling of low achievement), while there are no statistically significant differences in the dimension (loss of the human element) of functional combustion among employees of King Abdulaziz University and the University of Jeddah , it is also clear that the functional combustion of employees of King Abdulaziz University is more than the University of Jeddah, due to the presence of various factors and causes that contribute to a strong degree in functional combustion and job dissatisfaction in the sample of the study.